The Effect of Work Rotation and Work Motivation on Employee Work Productivity: Systematic Literature Review Streght Based Assessment - Purwanggono, Cuk Jaka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The world of work demands Human Resources to work with speed and accuracy, and consider efficiency in all areas of work to increase productivity. Every employee has a different work spirit. The company has its own goals, both companies engaged in services or goods. For this reason, companies need to develop and manage their human resources. This study aims to review the impact given by doing Job Rotation both positive and negative impacts and to analyze how much work motivation affects employee work productivity. Job rotation and work motivation occur because there is a turnaround, or the emergence of changes in other job positions between two or more parties.